Production Behavior of Hydrate-Bearing Sediments with Mixed Fracture- and Pore-Filling Hydrates - Yaobin Li; Xin Xin; Tianfu Xu; Yingqi Zang; Zimeng Yu; Huixing Zhu; Yilong Yuan (Journal of Marine Science and Engineering, 2023)
Most hydrate-bearing sediments worldwide exhibit mixed pore- and fracture-filling hydrates. Due to the high exploitation value, pore-filling hydrate production is the focus of current hydrate production research, and there is a lack of systematic research on the decomposition of fracture-filling hydrates and their effects on the evolution of temperature and pressure in hydrate-bearing sediments. If only the decomposition characteristics of pore-filling hydrates are studied while the fracture-filling hydrates decomposition and its effects on the hydrate-bearing sediments production process are ignored, the obtained research results would be inconsistent with the actual situation. Therefore, in this study, the effects of fracture-filling hydrates with different dipping angles on the hydrate production process were studied, and the necessity of considering the phenomenon of mixed pore- and fracture-filling hydrates in hydrate-bearing sediments was illustrated. On this basis, the simulation of a typical site (GMGS2-16) with mixed pore- and fracture-filling hydrates was constructed, and the production process was researched and optimized. The results indicated that: (a) fracture-filling hydrates formed in shallow fine-grained sediments and gradually approached the area of pore-filling hydrates, before a stable mixed zone was formed; (b) the occurrence of fracture-filling hydrates was conducive to the hydrate-bearing sediment depressurization production, and the promoting effect of the fracture-filling hydrate with smaller dipping angles was stronger; and (c) depressurization combined with heat injection could effectively compensate for the local low temperature and secondary hydrate caused by the mass decomposition of fracture-filled hydrates.